Longitudinal qPCR Study of the Dynamics of L. crispatus, L. iners, A. vaginae, (Sialidase Positive) G. vaginalis, and P. bivia in the Vagina - Lopes dos Santos Santiago, Guido; Tency, Inge; Verstraelen, Hans; Verhelst, Rita; Trog, Marijke; Temmerman, Marleen; Vancoillie, Leen; Decat, Ellen; Cools, Piet; Vaneechoutte, Mario (PloS one, 2012)
To obtain more detailed understanding of the causes of disturbance of the vaginal microflora (VMF), a longitudinal study was carried out for 17 women during two menstrual cycles. Vaginal swabs were obtained daily from 17 non-pregnant, menarchal volunteers. For each woman, Gram stains were scored, the quantitative changes of 5 key vaginal species, i.e. Atopobium vaginae, Lactobacillus crispatus, L. iners, (sialidase positive) Gardnerella vaginalis and Prevotella bivia were quantified with qPCR and hydrogen-peroxide production was assessed on TMB+ agar. Women could be divided in 9 subjects with predominantly normal VMF (grades Ia, Ib and Iab, group N) and 8 with predominantly disturbed VMF (grades I-like, II, III and IV, group D). VMF was variable between women, but overall stable for most of the women. Menses were the strongest disturbing factor of the VMF. L. crispatus was present at log7-9 cells/ml in grade Ia, Iab and II VMF, but concentrations declined 100-fold during menses. L. crispatus below log7 cells/ml corresponded with poor H(2)O(2)-production. L. iners was present at log 10 cells/ml in grade Ib, II and III VMF. Sialidase negative G. vaginalis strains (average log5 cells/ml) were detected in grade I, I-like and IV VMF. In grade II VMF, predominantly a mixture of both sialidase negative and positive G. vaginalis strains (average log9 cells/ml) were present, and predominantly sialidase positive strains in grade III VMF. The presence of A. vaginae (average log9 cells/ml) coincided with grade II and III VMF. P. bivia (log4-8 cells/ml) was mostly present in grade III vaginal microflora. L. iners, G. vaginalis, A. vaginae and P. bivia all increased around menses for group N women, and as such L. iners was considered a member of disturbed VMF. This qPCR-based study confirms largely the results of previous culture-based, microscopy-based and pyrosequencing-based studies.